Marginal Utility and Exchange Value - Padan, R. S. (Journal of Political Economy, 1905)
The Austrian theory derives advantage from conceiving cost as well as product under the aspect of value. Utility is taken as the sole source of value, and a specific function -namely, marginal utility -is made the definite regulator, or determinant of the latter.' Cost of production being expressed in terms of value, the various factors enter into the problem under a single category, and thus it becomes a rational tundertaking to attempt a definite correlation. The fundamental thesis, the determination of value by marginal utility once accepted, the remainder seems easy. Value conceived as originating in the product is reflected in a faithful image to the paraphernalia of production. The opponents of the doctrine have too often adhered to the sacrificial conception of cost, and have essayed to establish an equation between things generically unlike. Interpreting cost of production as personal irksomeness, pain, and the like, they have vainly sought to, hold these elusive abstractions up to a concrete standard of measurement. The result has been that able men, although starting with a good working intuition that marginal utility is not the adequate solvent of exchange value, have ill succeeded in conductinlg their argument with clearness of thought and soundness of logic. For instance, Professor Macvane is led to drawing the inference that, " so, far froml controlling exchange value, it [marginal utility] is itself controlled by exchange value." 2 Now, under the hypothesis that exchange value and marginal utility have a common measure, there is no objection to saying that the measure of the latter is determined by that of the former, 1-" Value" in these Austrian formulae is, of course, not free from the suspicion of ambiguity, which, if well founded, discredits the results. This paper concerns itself with exchange value only; but, as the Austrian terminology is of necessity largely employed, misapprehension is guarded against by using the full -designation wherever the meaning might otherwise be doubtful.